Evaluation of Internal and Marginal Accuracy (Trueness and Precision) of Laminates Using DLP Printing and Milling Methods - Mijun Noh; Habin Lee; Wansun Lee; Jaehong Kim; Jihwan Kim (Biomimetics)
This study evaluated the internal and marginal accuracy (trueness and precision) of zirconia laminate veneers fabricated using the DLP printing and milling method, employing 3D analysis software program. The maxillary central incisor tooth of a typodont model was prepared by a dentist and scanned using a desktop scanner. An anatomical zirconia laminate was designed using computer-aided design (CAD) software and saved in a standard tessellation language (STL) format. Thirty zirconia laminates were manufactured using a milling machine (MLL group) and a DLP printer (PTL group). All the specimens were scanned, and their internal and marginal areas were edited accordingly. The root-mean-square value was used to assess the accuracy of the internal and marginal areas of the zirconia laminates. Statistical significance was evaluated using the Mann–Whitney U test. Statistically significant differences were found in RMS values for both groups in the internal and marginal areas (p < 0.001 and p = 0.034, respectively). The MLL and PTL groups differed significantly in terms of precision (p = 0.017), but not at the margin (p = 0.361). DLP-printed zirconia laminates demonstrated stable and consistent performance, making the technique a reliable option for producing esthetic prostheses.